2008
DOI: 10.1016/j.rmed.2008.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Aging and induced senescence as factors in the pathogenesis of lung emphysema

Abstract: Classically, the development of emphysema in chronic obstructive pulmonary disease is believed to involve inflammation induced by cigarette smoke and leukocyte activation, including oxidant-antioxidant and protease-antiprotease imbalances. While there is substantial evidence for this, additional aspects have been suggested by a number of clinical and experimental observations. Smokers exhibit signs of premature aging, particularly obvious in the skin. The link between aging and chronic disease is well-known, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
80
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(85 citation statements)
references
References 258 publications
(251 reference statements)
4
80
0
1
Order By: Relevance
“…During aging, reactive oxygen species (ROS) production and oxidant burden increase in lungs, contributing to parenchymal lung destruction and emphysema (17,18). Pulmonary emphysema may result from accelerated and premature aging of the lungs because of cellular senescence (19), consistent with the observation that most COPD patients develop disease at advanced ages.…”
mentioning
confidence: 58%
“…During aging, reactive oxygen species (ROS) production and oxidant burden increase in lungs, contributing to parenchymal lung destruction and emphysema (17,18). Pulmonary emphysema may result from accelerated and premature aging of the lungs because of cellular senescence (19), consistent with the observation that most COPD patients develop disease at advanced ages.…”
mentioning
confidence: 58%
“…Emphysema accompanies cellular senescence, and the incidence of this disease increases with age (Karrasch, Holz, & Jörres, 2008; Tsuji et al, 2006). Recent studies on the genetic and pharmacological ablation of senescent cells have demonstrated that these cells underlie several diseases (He & Sharpless, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Of the potential unique environmental factors, tobacco smoke is known to promote aging processes and cellular senescence (38) and telomere shortening (8) in addition to its known damaging effects on lung function (39). We found that current smoking, but not previous smoking was significantly associated with lung function variables FEV 1 , PEF and the FEV 1 /FVC ratio, but not FVC or LTL, and that smoking had a minor influence on the genetic and environmental components of the lung function variables, as observed previously (12).…”
Section: Discussionmentioning
confidence: 99%